2022
DOI: 10.3390/coatings12091297
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Particle Interaction with Surface Microdefects during Cold Gas-Dynamic Spraying

Abstract: The cold gas-dynamic spray (CGDS) technique is utilized for repairing processes of a large number of metallic components in mechanical and process engineering, such as bridges or vehicles. Fine particles impacting on the component surface can be severely deformed and penetrate into the defects, filling and coating them, resulting in possible protection against corrosion or crack propagation. This work focuses on the investigation of the impact behavior of cold sprayed particles with the wall surface having mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…When the diameter is 50 µm, the maximum PEEQ increases in the range of 500~550 m/s and decreases at the velocity of 650 m/s. Studies [37,43,57] have further shown that when the particle size increases to a certain size, its critical velocity decreases. Larger particles are more likely to deposited when the velocity of particles with small size also decrease equally; due to their higher critical velocity than the corresponding critical velocity of large particles, small particles may not be able to deposit on the substrate.…”
Section: Effect Of Particle Size On Deformationmentioning
confidence: 99%
“…When the diameter is 50 µm, the maximum PEEQ increases in the range of 500~550 m/s and decreases at the velocity of 650 m/s. Studies [37,43,57] have further shown that when the particle size increases to a certain size, its critical velocity decreases. Larger particles are more likely to deposited when the velocity of particles with small size also decrease equally; due to their higher critical velocity than the corresponding critical velocity of large particles, small particles may not be able to deposit on the substrate.…”
Section: Effect Of Particle Size On Deformationmentioning
confidence: 99%
“…Metallurgical bonding has been observed using various microstructural characterization techniques [17,27,47,52,53,[55][56][57]. These include scanning and transmission electron microscopy [55,58,59] and various empirical models [48,56,57] have been developed to explain the mechanism. The schematic representation of the bonding mechanism of a typical cold spray process (tantalum particle on 4340 steel substrate) is given in Figure 6.…”
Section: Bonding Mechanisms Of Cold Spray Of Metallic Materialsmentioning
confidence: 99%
“…Metallurgical bonding has been observed using various microstructural characterization techniques [17,27,47,52,53,[55][56][57]. These include scanning and transmission electron microscopy [55,58,59] and various empirical models [48,56,57] have been developed to explain the mechanism.…”
Section: Bonding Mechanisms Of Cold Spray Of Metallic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most other simulations were performed using Johnson-Cook strain-rate plasticity model, for example, by Yokoyama (2006) and Mebdoua et al (Mebdoua, Fizi & Bouhelal, 2016), and the impact of a particle coming into contact at an angle by Li et al (2007). Simulations of a particle falling into a crack in material were performed by Aleksieieva et al (2022). An attempt to simulate the impact by using different plasticity models, that is, closer to experimental high strain rate results, was made by Razavipour and Jodoin (2021).…”
Section: Numerical Methods In Simulation Of Particle Interactionmentioning
confidence: 99%